2003
DOI: 10.1007/s00436-002-0719-z
|View full text |Cite
|
Sign up to set email alerts
|

A method to obtain axenic Angiostrongylus vasorum first-stage larvae from dog feces

Abstract: An improved method to obtain a large number of axenic larvae of Angiostrongylus vasorum from fecal samples was developed in the present study. The procedure here in reported consisted of obtaining larvae using a modified Baermann technique, followed by an additional filtration step. This isolation technique recovered almost 90% of the living larvae in a clean preparation. Isolated larvae were submitted to decontamination treatments with either sodium hypochlorite or antibiotic cocktail solutions. The axenic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…These results corroborate those of Bessa et al [7], Oliveira-Júnior et al [30], and Barçante et al [16], who observed a prepatent period varying from 28 to 108 days afterinfection. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results corroborate those of Bessa et al [7], Oliveira-Júnior et al [30], and Barçante et al [16], who observed a prepatent period varying from 28 to 108 days afterinfection. …”
Section: Discussionsupporting
confidence: 92%
“…The feces of infected dogs was collected, and L1 were recovered by the modified Baermann apparatus [16]. After 24 hours of fasting, mollusks were individually placed in polystyrene culture test plates with 24 wells of 15 mm diameter (TPP—Techno Plastic Products, Switzerland) and fed with 250 L1 on a fragment of lettuce (approximately 15 mm diameter).…”
Section: Methodsmentioning
confidence: 99%
“…Three weeks prior to inoculation, all foxes were treated with fenbendazole (50 mg/kg BW/day orally for 3 days, Panacur®). Faecal examination by a modified Baermann method [26, 27] confirmed that they were free from metastrongyloid infections prior to study start. Foxes were fed daily with 300–350 g of a commercial wet feed based on chicken, fish and plant material with energy content of 1,900 kcal/kg and they had access to water ad libitum .…”
Section: Methodsmentioning
confidence: 99%
“…A total of five Sprague-Dawley (SD) rats were infected by intragastric injection of 50-80 L 3 . Thirty-five days post-infection, fresh faeces (i.e., not older than 12 h) were collected from infected rats and the L 1 larvae were isolated by the Baermann technique [5]. Eggs of P. canaliculata were cultured in the laboratory to make certain that developing snails remained uninfected throughout the study.…”
Section: Resultsmentioning
confidence: 99%